Recovery of Flake Graphite from Kish - Kazmi, K. R.; Anwar, M. Shafique; Bhatti, M. Arif; Mehmood, Anar (Biological Sciences - PJSIR, 2007)
A l aboratory in vest i gation was made to recover h i gh q u al ity fl ake graphi te from th e steel maki n g wa t e . The waste, w hi ch i s ca l l ed Ki sh , i n iti a ll y contai n ed 65%, graph i t i c carbon . Ac id l each i n g tech n iq u e wa employed to pu ri fy t h e waste and i t was com pleted i n tw o steps u i n g 1-1 I and H F. Th i s paper deals wi th th e result s on th e opti mizati on of l each i n g pa ra m eters l i k e ac i d con centration , liq uid to sol i d r at i o, t i me and tem peratu re. Fi rst l each i n g w i th H CI L1pgrnd ed t h e K i h to 92.4 % 99.74% recovery, wh i l e second l each i n g w i th HF fu rth er i mproved the grade u p to 99.38% @ recovery 99.89%.